Quantification of pyrethroid and organophosphate metabolites in hair and urine samples of rural children from the Western Cape, South Africa using the two-dimensional gas chromatography-mass spectrometry - Mugari, Mufaro (Department of Medicine, 2025)
Extensive use of organophosphates (OPs) and pyrethroids (PYRs) in the Western Cape's farming regions raises significant health concerns, particularly for children, whose developing bodies are more susceptible to the toxic effects of these chemicals. Regular monitoring of these insecticide concentrations in human biological matrices is essential to identify and minimize exposure risks. However, existing chromatography monitoring systems encounter challenges such as sensitivity and matrix effects when quantifying these compounds in complex biological samples. This study evaluated a two-dimensional gas chromatography coupled with a time-of-flight mass spectrometry (2-D GCxGC TOF/MS) based method, specifically designed for analysis of compounds in complex matrices such as urine and hair matrices. Furthermore, the 2D GCxGC TOF/MS was available in-house and proved to be less expensive than outsourcing an analysis using a triple quadrupole mass spectrometer. The development and validation of the analysis method involved several key steps. First, the extraction techniques were optimized, utilizing QuEChERS for urine samples and solid-liquid extraction for hair samples. This was followed by the fine-tuning of metabolite derivatization using N-tert- butyldimethylsilyl-N-methyltrifluoroacetamide (MTBSTFA) to ensure efficient analysis. The choice of extraction methods was tailored to each sample type to maximize recovery and data reliability. Additionally, MetaboAnalyst 5.0 was used on non-targeted analysis data, offering insights into exposure variations and the effects of OP and PYR exposure on metabolic pathways. Both targeted and non-targeted analysis was performed using 2-D GCxGC TOF/MS. The study focused on children from farming areas in Grabouw and the Hex River Valley, monitored over two cycles (2017 and 2018). The developed and validated method was applied to urine samples (n = 122) collected from 61 participants and hair samples (n = 176) collected from 176 children. Alongside these biological samples, detailed demographic, geographic, and agricultural practice data were collected to provide a comprehensive context for the analysis. The 2-D GCxGC TOF/MS technique demonstrated a limit of detection (LOD) ranging from 0.19 to 0.89 ng/mL and a limit of quantification (LOQ) ranging from 0.58 to 2.69 ng/mL for the targeted metabolites (dimethylphosphate-DMP, diethylphosphate-DEP, dimethylthiophosphate-DMTP, diethylthiophosphate-DETP, and 3-phenoxybenzoic acid-3PBA). Additionally, the method detection limit (MDL) for urine samples were between 0.16- 5.96 ng/mL and MDL for hair were between 2.27- 99.45 pg/mg. Although the LOD and LOQ in this study were higher than those typically reported using liquid chromatography-mass spectrometry (<0.1 ng/mL), the method effectively detected OP and PYR exposure levels in children from farming areas in the Western Cape, where agricultural activities lead to elevated exposure. Although extraction recoveries in this study were generally above 50%, the results remained below the typical range of 70-130 %. This could be due to complexity of polar metabolites within the urine matrix likely contributed to inefficient interactions with derivatization agents, additionally, the derivatization process also altered the properties of the analytes and matrix components, further reducing recovery rates. Ethyl acetate proved to be the most effective solvent for enhancing extraction and detection rates. The method was applied to the samples and the analysis showed OP and PYR metabolites in 50% of urine samples and 38% of hair samples. The method's robustness was demonstrated by its ability to detect and quantify metabolites at low levels. Universal exposure to OPs and PYRs among the children was indicated, likely driven by seasonal and agricultural practices. Notable findings included the detection of DMP, DEP, DETP, and 3-PBA at varying concentrations, suggesting episodic exposure events. The integration of MetaboAnalyst 5.0 with 2-D GCxGC TOF/MS provided a detailed examination of the metabolic pathways affected by insecticide exposure which revealed alterations in amino acid concentrations including glycine, serine, and threonine, suggesting potential disruptions in protein synthesis, energy metabolism and the nuanced biochemistry of human exposure to OPs and PYRs. Furthermore, non-targeted analysis revealed subtle shifts in the abundance of various metabolites involved in oxidative stress response and xenobiotic metabolism pathways, providing insights into the biochemical effects of OP and PYR exposure in children. The study demonstrated the efficiency of 2-D GCxGC TOF/MS in detecting and quantifying OP and PYR metabolites in biological samples, highlighting its potential for broader environmental and health research. The findings suggest potential geographical and agricultural practice-based variations in exposure levels, warranting further investigation into the nature of OP and PYR exposure in the region. Furthermore, the integration of analytical tools like MetaboAnalyst 5.0 enhanced the understanding of the metabolic impacts of OP and PYR exposure thus prepares for further research groundwork in this crucial field. This supports the need for customized biomonitoring strategies to manage the health risks of insecticide exposure in vulnerable groups, especially children. Continuous monitoring and advanced analytical methods are essential for safeguarding these at-risk populations.